Antimicrobial characterization of silver nanoparticle-coated surfaces by “touch test” method - Marianne Gunell; Janne Haapanen; Kofi J Brobbey; Jarkko J Saarinen; Martti Toivakka; Jyrki M Mäkelä; Pentti Huovinen; Erkki Eerola (Dove Medical Press, 2022)
Abstract: Bacterial infections, especially by antimicrobial resistant (AMR) bacteria, are an increasing problem worldwide. AMR is especially a problem with health care-associated infections due to bacteria in hospital environments being easily transferred from patient to patient and from patient to environment, and thus, solutions to prevent bacterial transmission are needed. Hand washing is an effective tool for preventing bacterial infections, but other approaches such as nanoparticle-coated surfaces are also needed. In the current study, direct and indirect liquid flame spray (LFS) method was used to produce silver nanoparticle-coated surfaces. The antimicrobial properties of these nanoparticle surfaces were evaluated with the “touch test” method against Escherichia coli and Staphylococcus aureus. It was shown in this study that in glass samples one silver nanoparticle-coating cycle can inhibit E. coli growth, whereas at least two coating cycles were needed to inhibit S. aureus growth. Silver nanoparticle-coated polyethylene (PE) and PE terephthalate samples did not inhibit bacterial growth as effectively as glass samples: three nanoparticle-coating cycles were needed to inhibit E. coli growth, and more than 30 coating cycles were needed until S. aureus growth was inhibited. To conclude, with the LFS method, it is possible to produce nanostructured large-area antibacterial surfaces which show antibacterial effect against clinically relevant pathogens. Results indicate that the use of silver nanoparticle surfaces in hospital environments could prevent health care-associated infections in vivo.